Development of Lane Departure Warning Traffic System - Balashanmugam, P.; Balasubramanian, G.; Talukdar, Dipam; Roy, Rohit (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
In road-transport terminology, a lane departure warning system (LDWS) is a mechanism designed to warn a driver when the vehicle begins to move out of its lane on freeways and arterial roads. These systems are designed to minimize accidents by addressing the main causes of collisions: driving error, distraction and drowsiness. In this work the authors present a system which has the potential to reduce fatalities which are caused by the common type of crashes called the Run –Off-Road (ROR) crash. The work is to build a lane Departure Warning System for use on roads and highways. The functioning of the system will be to constantly monitor the car placement in relation to the road marks (with the aid of infrared proximity sensor), detect when the driver drifts away from the current lane without an appropriate warn signal, and provide a quick and effective alert to the driver to take a corrective action. To provide an alert system to trigger the quickest response possible. So the aim of this work is to make an intelligent system in hope to design a safer mean of transportation to save lives wasted on roads yearly, especially with the increase in the number of cars introduced to the roads each year. So the need of such security systems in today’s intelligent cars is essential.